2016
DOI: 10.1515/jeb-2016-0004
|View full text |Cite
|
Sign up to set email alerts
|

Economic Structure and Regional Economic Performance in Advanced Eu Economies

Abstract: Recent economic turmoil has revived interest in the quest

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In modern conditions, the study of structural transformations in the regions is of considerable importance, since the structural dynamics of the regional economic system determines its stability to external challenges and threats [8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…In modern conditions, the study of structural transformations in the regions is of considerable importance, since the structural dynamics of the regional economic system determines its stability to external challenges and threats [8][9][10][11][12][13].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it is widely known that manufacturing contributes to national development and regional development (Stojčić, Bezić, and Galović 2016). Therefore, concerns regarding the decrease of manufacturing share and the necessity of reindustrialization at the national and regional level routinely appear.…”
Section: Structural Changes and Specializationmentioning
confidence: 99%
“…Bo Zhang (2015) analyzed the impact of industrial structure on economic growth in Japan, and the empirical results show that the speed of adjustment of industrial structure has a positive role in promoting the economic growth [5]; Stojčić Nebojša eta al. (2016) investigated the relationship between economic structure and regional economic structure in the ten EU Member States after crisis, and distinguished the effects of economic structure in and intra-region [6]. X Li et al (2017) compared different regions, and showed that the optimization of the industrial structure has obvious regional characteristics of impact on economic growth [7].…”
Section: Introductionmentioning
confidence: 99%